PROPERTIES OF EUCALYPTUS INTERTEXTA WOOD GROWN IN SOUTHERN REGION OF IRAN - Abdolrahman Hosseinzadeh (Regional Information Center for Science and Technology (RICeST), 2001)
Eight-nineteen-year-old trees from Eucalyptus intertexta from Sarab bahman experimental Plantation located 160 Km. South west of Shiraz were selected randomly and fell two from each of the four blocks. Form each tree, 10 cm. thick cross-sectional discs at several different heights (3 meters intervals) were cut and together with remaining boles then transferred to the Alborz Research Center-Karaj for laboratory studies. The laboratory studies included determination of physical, anatomical and mechanical properties as well as chemical compositions of wood. The mechanical properties were evaluated on the ASTM methods for air-dry and green conditions. The following conclusions were drawn from this study:E. intertexta from one site in southern region of Iran has an average specific gravity of 0.86, fiber length of 0.71 mm, fiber diameter of 25.26 mm, lumen diameter of 4.04 mm, cell wall thickness 5.62 mm, cellulose content of 45.95; lignin 28.2; extractives soluble in alcohol - Banzen 4.28 and ash 0.62 percent.It was found that the mean values of modulus of rupture, modulus of elasticity and compression strength-parallel to grain tested at green condition were 74.21 MPa, 8454 MPa and 38.52 MPa and air-dried condition were 123.47 MPa, 14667 MPa and 77.99 MPa respectively. Data are also presented on other mechanical properties such as impact strength, nail withdrawal cleavage and etc.